Motif Bunuh Diri Mahasiswa Inisial CA Berdasarkan Eksistensialisme Jean Paul Sartre - Harfiani, Malihah; Syihabuddin, Syihabuddin (Peneliti.net, 2024)
The increase of suicides in Indonesia, especially those involving university students, has been in the public attention. In the context of Sartre's existentialism, suicide is considered the result of an individual's absolute freedom and crisis of existence. This research focuses on analyzing the motive of CA's suicide through the letter he left behind, using the theoretical concept of Sartre's existentialism. The research method used was descriptive qualitative with a phenomenalogical approach to the suicide motive revealed in the letter. The results showed that there were four concepts of Sartre's existentialism described in the suicide motive left by CA, including existence precedes essence, subjectivity, freedom, and responsibility.